1998
DOI: 10.1002/(sici)1096-8628(19980305)76:2<133::aid-ajmg5>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Blepharo-cheilo-dontic (BCD) syndrome: Report on four new patients

Abstract: We report on four Brazilian patients with, among other signs, cleft lip and palate, dental anomalies, ectropion of the lower eyelids, euryblepharon, and lagophthalmia. Two were sporadic cases and two were familial cases, a mother and her equally affected son. Recently, the reports with different combination of these signs were reviewed by Gorlin et al. [1996; Am J Med Genet 65:109-112] and named blepharocheilo-dontic (BCD) syndrome. Variable expressivity and autosomal dominant inheritance were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
(3 reference statements)
2
6
0
Order By: Relevance
“…In our patient, all the deciduous teeth were missing, and only four tooth buds of permanent molars were present symmetrically. It is possible that molar tooth buds will be produced hereafter, and the type of oligodontia will be similar to that reported by Martinez et al (1987) and Guion-Almeida et al (1998).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In our patient, all the deciduous teeth were missing, and only four tooth buds of permanent molars were present symmetrically. It is possible that molar tooth buds will be produced hereafter, and the type of oligodontia will be similar to that reported by Martinez et al (1987) and Guion-Almeida et al (1998).…”
Section: Discussionsupporting
confidence: 53%
“…Gorlin et al (1996) originally proposed this syndrome; they reviewed reports published before 1996 of patients with a similar presentation, and concluded that 12 cases (Piper, 1957;Allanson and Mc-Gillivary, 1985;Martinez et al, 1987;Falace and Hall, 1989; 8 cases of Korula et al, 1995) could be classified as BCD syndrome. Since then, 21 cases have been reported, including the patient discussed here: 8 by Gorlin et al (1996; case 3, however, was the same patient reported by Piper in 1957), 4 by Guion-Almeida et al (1998), 2 by Valdez et al (1999, 1 by Yen et al (2001), 3 by Lopes et al (2003), 1 by Martinhago and Ramos (2004), and 1 by Salinas and Bray (2004). Only 32 cases, therefore, have been reported (Table 1).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The blepharo-cheilo-dontic (BCD) syndrome consists of lagophthalmia, ectropion of the lower eyelids, distichiasis, euryplepharon, cleft lip/palate, and oligodontia. The BCD syndrome has autosomal dominant inheritance with variable expression [Martínez et al, 1987;Gorlin et al, 1996;Guion-Almeida et al, 1998;Valdéz-de la Torre et al, 1999]. At present, a gene for BCD syndrome has not been identified.…”
Section: Research Lettermentioning
confidence: 99%